THE RELATION OF ERYTHROCYTE SPHERICITY WITH MEMBRANE PROTEINS IN ARTERIAL HYPERTENSION - A. S. Sergeeva; Yu. I. Pivovarov; I. V. Babushkina; L. A. Dmitrieva (Российский кардиологический журнал)
Aim. To study the relation of the pattern of erythrocyte sphericity value changes and the levels of structural and functional proteins of erythrocyte membrane in patients with arterial hypertension (AH).Material and methods. Totally, 51 patient participated with AH of 1 and 2 grade (mean age 42±1,5 y.), in whom we assessed sphericity of erythrocytes (SE) and performed quantitative evaluation of 10 membrane proteins of erythrocytes. Analysis of the acquired data was done via non- and parametrical statistics methods.Results. All AH patients were selected to a group with “normocytosis” (SE ≥3,4 U) and “spherocytosis” (SE <3,4 U), that significantly differed by contents of α- and β-spectrines. Discrimination analysis revealed that the main influence on the separation of these 2 groups had the following proteins: α-spectrine, anion transport protein, tropomyosine and G-3-PDG. The same proteins were found as predictors of SE deviations in models under regression analysis.Conclusion. It was shown, that the amount and relation of various cytosceletal and functional proteins in erythrocyte membrane of AH patients might determine the changes of stability and deformability of the membrane itself, that also promotes the development of significant erythrocyte dysfunction in general and complication of systemic hypoxia in this category of patients.